Leveraging Renewable Energy and ESG for a Sustainable Future: The Mediating Role of Green Accounting in Carbon Emission Management and the Green Economy - Silaban, Adanan; Sitorus, Sunday Ade (International Journal of Energy Economics and Policy, 2025)
The increase in global carbon emissions, especially from the energy sector, has created major challenges to environmental and economic sustainability. In Medan City, the dominance of fossil-based energy, the low adoption of Renewable Energy, and the suboptimal application of ESG are obstacles in realizing green economic development. Green Accounting is considered a strategic approach to improve transparency and efficiency in corporate environmental management. This study uses a quantitative approach with the Structural Equation Modeling (SEM) method. Primary data is obtained from a survey of 300 companies in Medan that implement sustainability aspects, while secondary data comes from sustainability reports, ESG, and carbon emissions. The analysis includes direct, indirect, and total effects among the variables of Renewable Energy, ESG, Green Accounting, Green Economy, and Carbon Emission Management.Results show that Renewable Energy has a significant effect on Green Economy directly and through the mediation of Green Accounting, although it is not significant on Green Accounting directly. ESG has a significant effect on Carbon Emission Management both directly and through Green Accounting, but not significantly on Green Economy. Green Accounting plays an important mediating role that strengthens the influence of Renewable Energy and ESG on Carbon Emission Management and Green Economy. However, implementation challenges include low ESG literacy, limited supporting policies, and technology investment. Renewable Energy and ESG have great potential in supporting green economy development and carbon emission management through the integration of Green Accounting. This research recommends incentive policies, improved ESG literacy, and cross-sector collaboration to accelerate the transition to sustainability.